Persistence of poverty in an indigenous community in Southern India: Bringing agrarian environment to the centre of poverty analysis - Sudheesh Ramapurath (United Nations Research Institute for Social Development (UNRISD), 2019)
This paper draws attention to the need for centring the agrarian environment in poverty analysis and development policymaking. Through an ethnographic enquiry into the persistence of poverty among a landless indigenous community in the southern Indian state of Kerala, this paper tries to understand the community's negotiations with changes in the agrarian environment. The community is losing out on livelihood strategies and adaptation measures on multiple fronts simultaneously. The multi-directionality and simultaneity of the exclusions produced by changes in the agrarian environment warrant attention in poverty analysis, the paper argues. I follow members of this community in their quest to find alternative livelihoods in the wake of rapid deagrarianization in Kerala and show how they are systematically losing out on each of these livelihood pathways. I also follow them in sites of migration in the villages of the neighbouring state of Karnataka, where they are fast being replaced by cheaper labour. Fieldwork in sites of state-sponsored land distribution shows that receiving land does not necessarily work towards lifting them out of precarity. From these observations, the paper concludes that the stealthy ways in which changes in the agrarian environment further the exclusions of marginalized communities need to be paid greater attention.
Keywords: 330; Agrarian change; indigenous peoples; land; poverty; environment